Implementasi Kebijakan Program Duta Desa Digital di Desa Simangambat Julu - Tanjung, Sahrinal; Wulandari, Novita (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
Village digitalization aims to improve public services and transparency of village government administration. The Digital Village Ambassador Program in Simangambat Julu Village is designed to accelerate the digitization of village services, facilitate access to information, and improve administrative efficiency. This study uses a descriptive qualitative method with interview, observation, and documentation techniques. The research informants consisted of village officials, cadres of Digital Village Ambassadors, and the community using digital services. The analysis was based on the Edwards III policy implementation model, which included four key indicators: communication, resources, disposition, and bureaucratic structure. The results of the study show that the Digital Village Ambassador Program has been running but has not been optimal. The main obstacles include low digital literacy, limited infrastructure, and a lack of continuous socialization and education. In addition, the absence of clear SOPs makes people prefer conventional services. Supporting factors for this program include village government support, national regulations, and increasing public awareness of the benefits of digitalization. To optimize the program, digital education, infrastructure improvements, strengthening policies and SOPs, and increasing budget allocation are needed.